2020
DOI: 10.1007/s42773-020-00056-0
|View full text |Cite
|
Sign up to set email alerts
|

Electrical conductivity of wood biochar monoliths and its dependence on pyrolysis temperature

Abstract: Biochar is traditionally used as solid fuel and for soil amendment where its electrical conductivity is largely irrelevant and unexplored. However, electrical conductivity is critical to biochar's performance in new applications such as supercapacitor energy storage and capacitive deionization of water. In this study, sugar maple and white pine were carbonized via a slow pyrolysis process at 600, 800 and 1000 °C and conductivities of monolithic biochar samples along the radial direction were measured using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(50 citation statements)
references
References 38 publications
6
38
0
2
Order By: Relevance
“…Biochar when carbonized at high treatment temperatures above 500 °C shows electrical conductivity. Gabhi, Kirk, and Jia (2017) [ 104 ], R. Gabhi et al (2020) [ 105 ] in their studies observed that carbonization of wood blocks at higher temperatures of 1000 °C leads to a subsequent increase in carbon content in the char. This temperature of pyrolysis and carbon content plays an important role in electrical conductivity of biochar.…”
Section: Composite Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Biochar when carbonized at high treatment temperatures above 500 °C shows electrical conductivity. Gabhi, Kirk, and Jia (2017) [ 104 ], R. Gabhi et al (2020) [ 105 ] in their studies observed that carbonization of wood blocks at higher temperatures of 1000 °C leads to a subsequent increase in carbon content in the char. This temperature of pyrolysis and carbon content plays an important role in electrical conductivity of biochar.…”
Section: Composite Propertiesmentioning
confidence: 99%
“…This temperature of pyrolysis and carbon content plays an important role in electrical conductivity of biochar. The study reported that biochar monoliths carbonized at 1000 °C had electrical conductivity between the range of 2300–3300 S/m [ 105 ]. Electrically conductive composites developed by Nan et al (2016) [ 33 ] reported electrical conductivity in biochar filled composites fabricated using solution casting method.…”
Section: Composite Propertiesmentioning
confidence: 99%
“…For example, for agronomic applications, a high electrical conductivity value indicates the presence of salts, where a high biochar application rate may have negative effects on salt-sensitive plants (Singh et al 2017). However, a high electrical conductivity value would be favourable for other applications such as supercapacitors for energy storage (Gabhi et al 2020;Abdel Maksoud et al 2020). Similar to pH, the type of feedstock and the processing conditions are determinants for the electrical conductivity values measured in the resulting biochar.…”
Section: Chemical Properties and Compositionmentioning
confidence: 99%
“…The poor conductivity of ind400ex resulting from the low carbonization and graphitization degree (Gabhi et al 2020(Gabhi et al , 2017) could be the reason for the weak current. Meanwhile, the composition characterization showed higher contents of amorphous aromatics with heteroatoms in st700ex (than st700re) and ind400re (than ind400ex), more condensed structures with fewer heteroatoms in st700re than in st700ex, and fewer aromatized carbons with more heteroatoms in ind400ex than in ind400re.…”
Section: Direct Link Between Eec and Structurementioning
confidence: 99%